Formação cultural, semiformação, indústria cultural: contribuições de Theodor W. Adorno para pensar a educação - Bandeira, Belkis Souza (2008)
This paper reflects on today s education based on Theodor Adorno s thought categories. It examines the Cultural Formation concept (Bildung) from the Enlightenment Period to contemporary Adorno s so-called Semi-formation (Halbbildung) and tries to demonstrate the relation between Education and Cultural Formation as interconnected processes. The basis for the consolidation of Adorno s Semi-formation process occurs when symbolic production, a characteristic of the cultural process, distances itself from genuine folklore and approaches market interests, turned into a commodity by the Cultural Industry. In this process, the subjective conditions that enable the consolidation of the emancipatory character of Formation are broken. This mercantilistic cultural phenomenon is characterized by Adorno as Cultural Industry, since it is not spontaneously produced by the masses but is rather an economic activity organized according to monopolist capitalist concepts, and legitimates control and integration patterns of social groups which are greatly different from each other. The paper also reflects on the de-sensibility process as well as the development of defense mechanisms that incite individuals to be indifferent to the atrocities they are submitted to daily. It proposes a reflection towards the development of critical thought to the model that prevails in a controlled society, firstly by trying to establish art as a bastion against instrumental reality and secondly by returning to the problem so as to reflect on the world of education, eventually understood through the mediation of the Cultural Formation (Bildung) proposal. The paper also takes into account that an aesthetic formation process, from an educational view, enables analyses of aesthetic elements of present-day society on a formative cultural context, updating art dialectically through the dynamic correlation which the aesthetic dimension has, not only as a significant expression of what is real, but also as a historical reality that expresses itself in a language that goes beyond the logic of instrumental reason, demanding other levels of perception and another dimension in the relation between man and his peers, the world, and nature. Also, from this Aesthetic view, it discusses the conception of a world that calls for another reasoning other than instrumental, with which reason is presently identified, rendering it blind to violence in various aspects of contemporary life.